Facing competition: Neural mechanisms underlying parallel programming of antisaccades and prosaccades. - Talanow, Tobias; Kasparbauer, Anna-Maria; Steffens, Maria; Meyhöfer, Inga; Weber, Bernd; Smyrnis, Nikolaos; Ettinger, Ulrich (Brain & Cognition, 2016)
The antisaccade task is a prominent tool to investigate the response inhibition component of cognitive control. Recent theoretical accounts explain performance in terms of parallel programming of exogenous and endogenous saccades, linked to the horse race metaphor. Previous studies have tested the hypothesis of competing saccade signals at the behavioral level by selectively slowing the programming of endogenous or exogenous processes e.g. by manipulating the probability of antisaccades in an experimental block. To gain a better understanding of inhibitory control processes in parallel saccade programming, we analyzed task-related eye movements and blood oxygenation level dependent (BOLD) responses obtained using functional magnetic resonance imaging (fMRI) at 3T from 16 healthy participants in a mixed antisaccade and prosaccade task. The frequency of antisaccade trials was manipulated across blocks of high (75%) and low (25%) antisaccade frequency. In blocks with high antisaccade frequency, antisaccade latencies were shorter and error rates lower whilst prosaccade latencies were longer and error rates were higher. At the level of BOLD, activations in the task-related saccade network (left inferior parietal lobe, right inferior parietal sulcus, left precentral gyrus reaching into left middle frontal gyrus and inferior frontal junction) and deactivations in components of the default mode network (bilateral temporal cortex, ventromedial prefrontal cortex) compensated increased cognitive control demands. These findings illustrate context dependent mechanisms underlying the coordination of competing decision signals in volitional gaze control.